Based on ACF-CFRP composite energy absorbing material protection clothing designing for the elderly with degenerative imbalance - Shifan Zhao; Lei Shen; Chuyue Liu; Han Chen (Journal of Engineered Fibers and Fabrics, 2024)
With the progression of age, the risk of falls in the elderly population escalates. Hip fractures are perceived as one of the most severe consequences of such falls and are often described as “the last fracture in one’s life,” with mortality rates reaching 20%−30% and accompanied by a significant rate of disability. To address this pressing issue, our study conducted an in-depth analysis of the mechanical properties of Artificial Cartilage Foam (ACF) and Carbon Fiber Reinforced Polymer (CFRP). Based on this research, we devised a laminated structure where ACF acts as the outer layer, with CFRP positioned centrally, capitalizing on the material’s intrinsic shock-absorbing attributes. Building on this structure, based on this structure, a specialized protective clothing design tailored for the elderly to counteract age-related balance impairments is proposed. Furthermore, we undertook experiments to gage user anxiety levels and assess the wearability comfort of the attire. Our findings indicate that this protective garment can effectively absorb the impact energy generated during falls, significantly reducing the risk of injury in the elderly. Additionally, its ergonomic design helps alleviate the psychological distress elderly individuals may experience due to the fear of falling. This research presents an innovative and effective strategy for enhancing fall protection in the elderly demographic.